Whistleblower Protection Models in Corruption Cases: A Legal Analysis of Reporting Mechanisms and Whistleblower Safety - Tumian Lian Daya Purba; Silvester Magnus Loogman Palit (Westscience Press, 2026)
Whistleblowers play a crucial role in exposing corruption, yet their effectiveness is often constrained by inadequate legal protection and ineffective reporting mechanisms. This study aims to analyze whistleblower protection models in corruption cases through a normative legal approach, focusing on the relationship between reporting systems and whistleblower safety. The research utilizes statutory, conceptual, and comparative approaches by examining legal instruments, doctrines, and best practices across jurisdictions. The findings reveal that although many legal systems have established formal whistleblower protection frameworks, significant gaps remain in their implementation, particularly in ensuring confidentiality, protection against retaliation, and access to reliable reporting channels. The effectiveness of whistleblowing systems is largely determined by the availability of secure, independent, and accessible reporting mechanisms, as well as the strength of institutional support and enforcement. Furthermore, whistleblower safety requires not only legal guarantees but also practical measures such as witness protection, psychological support, and financial safeguards. The study concludes that an integrated protection model—combining comprehensive legal frameworks, effective reporting mechanisms, and robust institutional coordination—is essential to enhance whistleblower participation and strengthen anti-corruption efforts.